Heat transfer performance of water-based tetrahydrofurfuryl polyethylene glycol-treated graphene nanoplatelet nanofluids - Arzani, H.K.; Amiri, A.; Kazi, S.N.; Badarudin, A.; Chew, B.T. (Royal Society of Chemistry, 2016)
In order to improve the colloidal stability of graphene nanoplatelets (GNPs) in aqueous media, GNPs were first functionalized with tetrahydrofurfuryl polyethylene glycol in a quick electrophilic addition reaction method. To assess this, surface functionalization of the GNPs was analyzed by FTIR and Raman spectroscopy, and thermogravimetric analysis. In addition, the morphology of treated samples was investigated by transmission electron microscopy (TEM). As the second phase of the study, the thermophysical properties of samples were experimentally investigated. The third phase of the study involved experimentally measuring and numerically simulating the convective heat transfer coefficient and pressure drop of water-based TFPEG-treated GNP nanofluids (TGNP/water) at various weight concentrations and comparison with the base fluid in an annular heat exchanger. The results suggest that the addition of TGNP into the water improved the convective heat transfer coefficient dramatically. The pressure drop of prepared samples illustrated an insignificant variation as compared with the base fluid. The steady-state forced convective heat transfer experiments and simulation have confirmed the promising cooling capabilities of TGNP/water.